Studies on ancient silver metallurgy using SR XRF and micro-PIXE. (December 2015) - Vasilescu, Angela; Constantinescu, Bogdan; Stan, Daniela; Radtke, Martin; Reinholz, Uwe; Buzanich, Guenter; Ceccato, Daniele
Abstract: This work presents a complex evaluation of a series of Geto-Thracian silver adornments found on Romanian territory, part of the 4th century BC Agighiol (Northern Dobruja) hoard and of an ingot from the 1st century BC Geto-Dacian Surcea (Transylvania) hoard, using Synchrotron Radiation X-Ray Fluorescence and micro- Proton Induced X-ray Emission analysis and mapping in order to investigate aspects related to the elemental composition of the metal and the metallurgy implied in their manufacture. One of the samples can be linked to Laurion as the source of metal, and several items contain silver probably originated in Macedonia. The set of silver items was found to be heteregenous as composition and microstructure, and corrosion-related elements could be also identified in the X-Ray maps. Highlights: SR XRF and μPIXE were used to investigate the composition and structure of ancient silver. Au and Bi are fingerprint elements, useful to identify metal sources. A Geto-Thracian silver sample is linked to the Laurion mine in Greece, by the Au/Ag and Bi/Ag ratio. Microstructure was correlated with metal-working techniques. Corrosion related traces of Br and Cl was identified by characteristic X-ray mapping.